Public Education Through Communication Campaigns in Enhancing Recycling Participation - Nurharisyah Hasibuan; Nursaima Harahap; Masrul Efendi Umar Harahap (CV. AFDIFAL MAJU BERKAH, 2024)
In the modern era, environmental issues have become a global concern, with waste management emerging as one of the primary focuses. This research aims to analyze the role of communication campaigns in public education to enhance students' participation in recycling activities. The study employs a Participatory Action Research (PAR) approach with a case study method to explore how communication campaigns can shape awareness, attitudes, and behaviors toward recycling. The findings indicate that effective communication campaigns, incorporating the use of social media, direct outreach, and collaboration with local communities, significantly improve students' understanding of the importance of recycling and motivate them to participate actively. Furthermore, the study reveals that recycling participation increases when communication campaigns are tailored to the local context and involve active student engagement. Consequently, the research concludes that public education through communication campaigns is a crucial strategy for enhancing recycling participation and contributing to environmental preservation, particularly at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. The implications of these findings highlight the need for more focused and sustainable communication campaigns to maximize the impact of public education on recycling participation.